The Accuracy of Indonesian Language Rules in Exam Questions Made by Teachers in Junior High School (SMPN) 27 Medan Academic Year 2016-2017 and 2017-2018 - Shara Novita; Wisman Hadi; Marice Marice (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Evaluation is the result of the teaching and learning process carried out by teachers and students. Assessment serves to measure students' understanding of the material given by the teacher. Evaluation or procurement activities also play an important role in improving the quality of learning. As for the accuracy of the use of the Indonesian language rules in the class and UAS test exam questions made by Indonesian Language teachers in SMP 27 for the last two years, namely in the total of 195 questions consisting of multiple-choice descriptions, it was found that 86 questions (44%) were not effective and 99 questions (51%) are effective. The most common mistake is the alignment and unity of ideas and economics. The accuracy of the use of the operational word in this study is quite good, because only 5 questions (3%) are incorrect and 190 other questions (97%) are stated correctly.